Inflammation in response to phytohemagglutinin injection in the Talas tuco-tuco (Ctenomys talarum): implications for the estimation of immunocompetence in natural populations of wild rodents - Merlo, Julieta (2014)
The immunological variation in wild populations and its relation to life-history traits has recently become a central topic in the field of evolutionary biology, considering the critical contribution of immunity to an individual’s fitness. A common technique used by ecologists to estimate immunocompetence in wild populations is the phytohemagglutinin (PHA) – skin test. In this test, the degree of local swelling triggered by PHA is usually considered an estimate of T-lymphocyte activity, although there is an ongoing debate regarding this interpretation. Here, we coupled the PHA–skin test with a histological analysis to examine the temporal development of the cell-mediated response in the subterranean rodent Talas tuco-tuco (Ctenomys talarum Thomas, 1898). The inflammation response involved lymphocytes, neutrophils, eosinophils, and macrophages at the site of injection, achieving an increase of total leukocytes from 12 to 48 h after injection. However, the abundance of any of the leukocytes observed did not correlate with the degree of swelling at any time studied, suggesting that caution should be taken when interpreting the results of the PHA-induced swelling response. Particularly, the magnitude of macroscopic swelling should not be considered a priori as indicative of T-lymphocyte activity in wild-caught rodents. Our results highlight the importance of avoiding oversimplified approaches to measuring immunocompetence.